2015
DOI: 10.1088/0953-4075/48/21/214002
|View full text |Cite
|
Sign up to set email alerts
|

Single-shot electron diffraction using a cold atom electron source

Abstract: Cold atom electron sources are a promising alternative to traditional photocathode sources for use in ultrafast electron diffraction due to greatly reduced electron temperature at creation, and the potential for a corresponding increase in brightness. Here we demonstrate single-shot, nanosecond electron diffraction from monocrystalline gold using cold electron bunches generated in a cold atom electron source. The diffraction patterns have sufficient signal to allow registration of multiple single-shot images, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…In the UCES high charge electron bunches are created by near threshold photo-ionisation of a cloud of laser-cooled and trapped atoms in a magneto optical trap (MOT) 22 . Previous work showed high quality diffraction patterns 23,24 with these bunches, demonstrating pulsed electron source temperatures as low [19][20][21] as a few-10 K. Additionally it was shown that it is possible to extract ultracold picosecond electron pulses 25 which can in principle be compressed to ∼ 100fs using well established RF compression techniques 26 .…”
Section: Introductionmentioning
confidence: 91%
“…In the UCES high charge electron bunches are created by near threshold photo-ionisation of a cloud of laser-cooled and trapped atoms in a magneto optical trap (MOT) 22 . Previous work showed high quality diffraction patterns 23,24 with these bunches, demonstrating pulsed electron source temperatures as low [19][20][21] as a few-10 K. Additionally it was shown that it is possible to extract ultracold picosecond electron pulses 25 which can in principle be compressed to ∼ 100fs using well established RF compression techniques 26 .…”
Section: Introductionmentioning
confidence: 91%
“…Careful ionization of an atomic ensemble, either directly or via a field-assisted process, produces inherently cold electron bunches, giving an impressively small transverse energy spread [8,9]. Electron beams with energies of U = 1-10 keV [10,11] have been produced by ionizing atoms in a static electric field, with the finite size of the ionization volume giving rise to a * scholten@unimelb.edu.au longitudinal energy spread on the order of 0.01% of the beam energy ( U = 0.1-1 eV). One possible mechanism to achieve reduced energy spread is field ionization of highly excited Rydberg atoms [12].…”
Section: Introductionmentioning
confidence: 99%
“…The next generation of CAES designs will be capable of significantly higher bunch charge, which will make single-shot measurements feasible, allowing for more precise measurements and permitting investigations of temporal bunch behavior in the femtosecond regime. By utilizing ultrafast ionization pathways in a CAES, ultrashort electron bunches can be generated [22,45] and the pepperpot-streaking system shown here could also prove useful in examining the efficacy of techniques to counter space charge expansion by observing the temporal behavior of space-charge driven emittance degradation [21]. This technique could serve as a powerful tool for the determination of time-resolved brightness for charged particle beams.…”
Section: Discussionmentioning
confidence: 99%